The Role of Consumers in Container Recycling in the Purified Water Industry - Banguera, Leonardo; Jiménez Peralta, Javier Alexi; García García, Cinthia Gabriela; Arcos Coba, Ángel Paulino (EASI: Engineering and Applied Sciences in Industry, 2025)
The sustainable management of plastic packaging in the purified water industry represents a significant environmental challenge, especially in Ecuador, where recycling infrastructure is insufficient and environmental education is limited. This study aims to analyze the behavior of millennial consumers in Guayaquil regarding plastic packaging recycling, identifying barriers and opportunities to strengthen their participation in the process. A mixed methodology was used, combining a review of scientific literature with structured surveys targeting millennials between 18 and 55 years of age to analyze their habits and perceptions regarding plastic packaging recycling. Survey results reveal that 65% of respondents regularly consume water in plastic containers, while 40% identify the lack of infrastructure as a significant barrier to recycling, and 60% are unaware of proper recycling practices. These findings underscore the need to develop comprehensive strategies that foster environmental education, optimize recycling infrastructure, and promote effective economic incentives, strengthen the circular economy and ensure the adoption of long-term sustainable practices in the purified water industry.